VCL505: Introduction to Visual Culture / College of Creative Arts - UiTM, College of Creative Arts (2023)
Visual Culture aims to introduce students to all aspects of culture that communicate through visual means within fine art or non-fine art disciplines. This course focuses on aspects of culture that rely on visual images as well as visual objects and their influences on society.